Slightly Acidic Electrolyzed Water Improves the Postharvest Quality of Litchi Fruit by Regulating the Phenylpropane Pathway - Xuanjing Jiang; Xiangzhi Lin; Yuzhao Lin; Yazhen Chen; Yihui Chen; Hongbin Chen (Horticulturae, 2025)
The market value of litchi fruit is declining quickly due to its susceptibility to disease and rapid pericarp browning. Slightly acidic electrolyzed water (SAEW) treatment is recognized as a safe disinfection technology that not only preserves the quality of postharvest produce, but also enhances disease resistance. This study assessed the efficacy of SAEW in preserving litchi fruit and boosting its resistance to disease. Litchi fruit underwent treatment with SAEW at various available chlorine concentrations (ACC) (10, 25, 50, and 75 mg/L) and subsequently stored at 25 °C for a duration of six days. The results revealed that SAEW with an ACC of 25 mg/L markedly improved the postharvest quality of litchi fruits, reduced disease incidence, and enhanced the appearance of the pericarp and nutrient levels in the arils. Additionally, this treatment enhanced the levels of disease resistance-related compounds, including lignin, flavonoids, and total phenolics, in the pericarp of litchis during the later storage stages (p < 0.05). Furthermore, in the final three days of storage, there were also noticeable increases (p < 0.01) in the activities of pericarp disease resistance enzymes (DREs), such as phenylalanine ammonialyase, cinnamate-4-hydroxylase, 4-coumarate CoA ligase, cinnamyl alcohol dehydrogenase, peroxidase, polyphenol oxidase, chitinase, and β-1,3-glucanase. Based on these results, it was concluded that SAEW triggered DRE activities and increased the accumulation of disease resistance-related compounds by regulating the phenylpropane pathway to suppress disease development, and elevated the storage quality of harvested litchi fruit. Consequently, SAEW has proven to be an effective and safe method for enhancing the storability of litchi fruit.